Almost Sure Exponential Stability of Large-Scale Stochastic Nonlinear Systems. Issue 5 (20th November 2018) - Barbata, Asma; Zasadzinski, Michel; Chatbouri, Ridha; Ali, Harouna Souley
ABSTRACT: This contribution deals with the study of the almost sure exponential stability of large-scale stochastic systems with multiplicative noises. Under a Lipschitz-like assumption, it is proven that this stability is guaranteed if each "diagonal" subsystem is almost surely exponentially stable.